Bank Financing of SMEs in Five Sub-Saharan African Countries The Role of Competition, Innovation, and the Government - Berg, Gunhild (The World Bank, 2013)
This paper provides an overview of the state of access to bank financing for SMEs in five Sub-Saharan African countries and analyzes the drivers behind banks' involvement with SMEs. The paper builds on data collected through five in-depth studies in Kenya, Nigeria, Rwanda, South Africa, and Tanzania between 2010 and 2012. The paper shows that the share of SME lending in the overall loan portfolios of banks varies between 5 and 20 percent. Reasons for this finding vary, but key contributing factors are the structure and size of the economy and the extent of Government borrowing, the degree of innovation mainly as introduced by foreign entrants to financial sectors, and the state of the financial sector infrastructure and enabling environment